An analysis of barriers to employee adoption of workplace health and safety standards at Eskom, Makhanda (Grahamstown) - Makholwane, Nobubele (Rhodes University, Faculty of Commerce, Rhodes Business School, 2019)
Workplace fatalities and injuries are a concern around the world, with over 2 million deaths because of workplace related activities. This makes safety culture in the workplace crucial to the sustainability of individuals, businesses and the society in general. Safety culture includes everything in the workplace, and is understood as common sense awareness and practice relating to safety. Central to developing a safety culture in an organization, is a good understanding of what safety problems existed in the past; what safety problems exist in the present, and what caused them, as well as what could be done to deal with those causes. The goal of this thesis, therefore, was to understand what barriers potentially exist for Eskom employees in Makhanda (Grahamstown) to understanding and adopting the company's safety policies and measures. A secondary aim was to explore different strategies for addressing these barriers. In order to get to the goal, it was important to; first, understand which aspects of Eskom's health and safety standards do employees have difficulty adopting. Second, it was important to investigate the specific barriers to employees' non-adoption of health and safety standards, by understanding their perceptions of safety issues in the workplace. Third, based on the findings, the study aimed to propose recommendations for improving the adoption of safety policies and measures by employees of Eskom. The key findings of the study include the fact that car accidents are the company's and employees major concern, but the employees also have many other concerns that they see as needing the company's attention (e.g. dealing with attacks on employees by customers; focusing on incentives rather than harsh enforcement for violators of safety policies). However, it is also clear that most employees do see safety as their responsibility as well. The two key areas of recommendations are, first, that leadership of Eskom adopt alternative leadership styles that focus more on ethical leadership, rather than transactional leadership that focus on profit margins more than it does on people. Second, it is recommended that Eskom provide incentives for compliance with safety policies; more training and education about safety; encouragement for Eskom to not put so much pressure on employees, who can lead fatigue; rather they should employ more people to do the jobs that the high pressure. To conclude, this research argues that neither do employees not employers think death and injuries are good for anybody. This is why this researcher is hopeful that this will get better, not worse, in terms of having a firm safety culture at Eskom as a workplace environment.
Keywords: Eskom (Firm) -- Employees -- South Africa -- Makhanda; Eskom (Firm) -- Management -- South Africa -- Makhanda; Industrial hygiene -- South Africa -- Makhanda; Employee motivation -- South Africa -- Makhanda